2012
DOI: 10.1007/s11051-012-1173-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of oxygen vacancies and Ce+3 concentrations in doped ceria nanoparticles via the selection of lanthanide element

Abstract: The effect of lanthanides that have positive association energies with oxygen vacancies, such as samarium and neodymium, and the elements with negative association energies, such as holmium and erbium, on ionization state of cerium and, consequentially, the oxygen vacancy concentration in doped ceria nanoparticles are investigated in this article. Structural and optical characterizations of the doped and undoped ceria nanoparticles, synthesized using chemical precipitation, are carried out using transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 29 publications
8
69
0
Order By: Relevance
“…Since only isolated defects were calculated, this could account for the disparity between the experimental and calculated frequencies. The possibility of the intrinsic surface peroxide species being present in reduced CeO 2 at high oxygen partial pressures may be significant for understanding CeO 2 catalysis, as previous studies have only considered reactions through the O vacancy [17,13,41] or through adsorbed peroxo/superoxo species. [42,43,40] Having demonstrated that alternative oxygen states to the O vacancy are valid defect structures on reduced pure CeO 2 surfaces, the La-doped CeO 2 surfaces were also investigated to examine whether these peroxide species are a viable mechanism for charge compensation.…”
Section: Resultsmentioning
confidence: 99%
“…Since only isolated defects were calculated, this could account for the disparity between the experimental and calculated frequencies. The possibility of the intrinsic surface peroxide species being present in reduced CeO 2 at high oxygen partial pressures may be significant for understanding CeO 2 catalysis, as previous studies have only considered reactions through the O vacancy [17,13,41] or through adsorbed peroxo/superoxo species. [42,43,40] Having demonstrated that alternative oxygen states to the O vacancy are valid defect structures on reduced pure CeO 2 surfaces, the La-doped CeO 2 surfaces were also investigated to examine whether these peroxide species are a viable mechanism for charge compensation.…”
Section: Resultsmentioning
confidence: 99%
“…The weak intensities occurring in the range 3550-3400 and 1600-1300 cm -1 can be assigned to O-H stretching vibrations of hydroxyl group, probably due to moisture content of KBr, as KBr is hydroscopic absorbs more humidity in the atmosphere. The strong bands at around 850-450 cm -1 can be attributed to characteristic Ce-O vibrations (Shehata et al 2012;Ainirad et al 2011;Arabaci and Oksuzomer 2012). The intensities of all other bands at 3550-3400 and 1600-1300 cm -1 have been reduced significantly because of high sintering temperature of 1100°C due to which the adsorbed water has been removed and improving the crystallinity of the samples.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Furthermore, Mg doping can lead to a higher abundance of Ce 4+ ions as compared to Ce 3+ ions in the CeO 2 matrix, which can also result in widening of its band gap. [39] To study the Mg doping induced effects on the electrical characteristics of CeO 2 nanostructures, the AC conductivities of all the prepared samples have been determined and shown in Figure 5. Figure 5 shows the variation of AC conductivity of all the prepared nanostructures as a function of AC frequency at room temperature.…”
Section: B Cell Culture and Treatmentmentioning
confidence: 99%